If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2(1 + -2x) = -1 4x + (1 * 2 + -2x * 2) = -1 4x + (2 + -4x) = -1 Reorder the terms: 2 + 4x + -4x = -1 Combine like terms: 4x + -4x = 0 2 + 0 = -1 2 = -1 Solving 2 = -1 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| (0.2x-0.3)(0.04x+3)=0 | | 9s^2+3s-20=0 | | p/d-c/d=1 | | 2y=x^2+3 | | 2x+95=6x+195 | | 2x+120-10x=-6x-20 | | -15+9m= | | 2(3n-1)=(9n+6)+4 | | 3/2|2x-5|-2=7 | | 21r^2+22r-8=0 | | 6y^2-9y+7=0 | | -4(t-2)+9t=3t-5 | | 0.18(y-9)+0.04y=0.12y-0.03(40) | | C=30(3.14) | | (4x+3)(2x-6)= | | 4t^2-40t+25=0 | | 3y=x^2+7 | | -2(1)+8=2 | | 4t^2-40+25=0 | | 0.2x=2.6x-2.8 | | Y=1/3(90-X)-6 | | Y=24-X/3 | | 10-4(3x+1)-(3x-4)= | | 6y-2x=1x | | 5-8x-2x=25 | | 2/7×-7 | | 1(1)-3(-2)+(-2)(-2)= | | 2/3(n-5/6)=5/2 | | 7/10=1/5x | | a1/3 | | 7/9(x-3/7)=7/3 | | 7/9*2 |